2022
DOI: 10.1001/jamanetworkopen.2021.42458
|View full text |Cite
|
Sign up to set email alerts
|

Weight-for-Height, Body Fat, and Development in Children in the East Asia and Pacific Region

Abstract: IMPORTANCE Weight-for-height z score (WHZ) is a standard indicator of children's nutritional status even though it does not fully reflect body fat. OBJECTIVE To examine the combined association of WHZ and body fat with early development in the East Asia and Pacific region. DESIGN, SETTING, AND PARTICIPANTS Children from the East Asia-Pacific Early Child Development Scales validation study, with full data available regarding their nutritional status and outcomes, were included in this cross-sectional analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Moreover, cumulative microbial ingestion may lead to chronic inflammation and can subsequently contribute to malnutrition and altered brain development, two conditions directly associated with ECD during the critical development period [6]. In fact, we previously showed the relevance of nutritional status on ECD using the EAP-ECDS data [25,26]. On the other hand, poor oral health is an important driver of caries, which is associated with speech problems, cognition, and overall development [6,13].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, cumulative microbial ingestion may lead to chronic inflammation and can subsequently contribute to malnutrition and altered brain development, two conditions directly associated with ECD during the critical development period [6]. In fact, we previously showed the relevance of nutritional status on ECD using the EAP-ECDS data [25,26]. On the other hand, poor oral health is an important driver of caries, which is associated with speech problems, cognition, and overall development [6,13].…”
Section: Discussionmentioning
confidence: 96%
“…In total, 149 million children under five years of age suffer from stunting (Global Nutrition Report, 2020;Laureati, 2022). In 2020, it was found that the total number of children suffering from stunting was 149.2 million (Petermann-Rocha et al, 2022). The problem of child stunting has recently gained public attention in Malaysia, but there is still a general lack of understanding about this issue (Kok, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As we can see, there are several forms of malnutrition. Most of the children suffered from thin (underweight) weight below the recommended level for a particular age; too thin (wasting) weight below the recommended level for a particular height; and short (stunting) height below the recommended level for a particular age (Petermann-rocha et al, 2022). All of these causes affect children's developing physical and mental that cause various forms of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Among the effects caused by this problem, stunting children is increasing and deserves attention. Petermann et al (2022) found that by 2020, approximately 149.2 million children will be stunting (Petermann-rocha et al, 2022). By 2025, the number of stunted children is estimated at 131 million (27 million exceeding the expected 40% reduction in the target number of stunting children) (Ali, 2021;Woreda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%